Teaching is … opening up spaces to explore academic work in fluid and volatile times. Issue 1 (2nd January 2017) - Sadler, Kirsten; Selkrig, Mark; Manathunga, Catherine
ABSTRACT: Universities are built upon the collaborative work of academic staff and students, yet the nature of this work has been undergoing profound and rapid change. Pressures within Australia's higher education sector have led to a fracturing of traditional academic roles and growing feelings of disconnection. While there have been many narrative, ethnographic and autoethnographic explorations of academic work, few studies have employed visual arts-informed methodologies to interrogate the ways in which academics represent their teaching, research and community engagement work. In this article we outline findings about academics' views of their teaching work. These findings surfaced from an arts-informed participatory research project, that sought to open up a space for (re)presentations of academic work. With a focus on teaching, three through lines emerged during the analysis: voicing absences and resistances; initiating layers of reflexive moments and expressing complexity through collage . We argue that the academics' responses allow us to trace the emotional terrain of contemporary academic work. They also open up ways to unpack, express and make visible academics' complex thoughts, feelings and ideas about teaching practices.